Rumen Content as Animal Feed: A Review (Journal of Veterinary Medicine and Animal Production, 2021)
The objective of this review is to highlight the nutritive value of rumen contents and their potential to use in animal feeds. In most developing countries feeding is the major factor limiting the production of livestock; because it constituents up to seventy percent of the total cost of production. In the last years, researchers look for non-conventional feed ingredients to reduce the feed cost and hence cost of production. One of such non-conventional ingredients is the rumen content, which is readily available in abattoirs and slaughter houses, it’s a good source of energy, protein (feed and microbial protein), minerals and vitamins specially vitamin B complex. The nutritive value of rumen contents varies mainly because the rumen content from different types of ruminants varies dramatically in their composition. The nutritive value of rumen content can be improved by using several methods: adding blood meal, molasses, poultry droppings, urea, enzymes and fermented feed such as silage. Rumen content can be added to diets by different levels according to the types of animals. It can be used as a cheap source of energy and protein with reduced feed cost and environmental pollution. Therefore, some studies concluded that rumen contents could be incorporated in the diets of animals without negative effects on diet acceptability and without any adverse effects on performance.
Keywords: Rumen content; Nutritive value; Anti-nutritional factors and replacement values